2007
DOI: 10.1152/ajpendo.00407.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of wortmannin on insulin's hemodynamic and metabolic actions in vivo

Abstract: Bradley EA, Clark MG, Rattigan S. Acute effects of wortmannin on insulin's hemodynamic and metabolic actions in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Clerk et al (20) described that fatty acid-induced insulin resistance in muscle is partially caused by impairment of insulin-mediated nutritive muscle blood flow (20), which is dependent on activation of phosphatidylinositol 3-kinase/Akt in muscle resistance arteries (19). These authors suggest a possible role for PKC in the impairment of insulin signaling in muscle resistance arteries (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clerk et al (20) described that fatty acid-induced insulin resistance in muscle is partially caused by impairment of insulin-mediated nutritive muscle blood flow (20), which is dependent on activation of phosphatidylinositol 3-kinase/Akt in muscle resistance arteries (19). These authors suggest a possible role for PKC in the impairment of insulin signaling in muscle resistance arteries (20).…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation, induced by fatty acids, has been shown to impair insulin-mediated glucose uptake in skeletal muscle myocytes and in adipocytes by the inhibition of Akt in in vitro studies (16 -18). As outlined above, however, impaired glucose uptake in muscle is also caused by impaired nutritive blood flow, which is critically dependent on activation of Akt (19). It has been reported that fatty acids directly impair insulin-mediated nutritive muscle blood flow and cause insulin resistance (20).…”
mentioning
confidence: 98%
“…Considering that inhibition of ACE or chronic blockade of AT1Rs is associated with increased levels of circulating ANG- (1)(2)(3)(4)(5)(6)(7), this hormone could be involved in the beneficial effects of antihypertensive therapy (15,26,44). The counterregulatory effects of ANG-(1-7) on the pressor and trophic actions of ANG II appear to be mediated by the Mas receptor (MasR), a G protein-coupled receptor present in several tissues, including heart and kidney (16,44).…”
mentioning
confidence: 99%
“…Tissues were prepared as described in Ref. 6, with the exception that protease inhibitor cocktail (Sigma) was added to the solubilization buffer. Protein (25 g) was then heated with 125 mM Tris·HCl, pH 6.8, 20% glycerol, 4% ␤-mercaptoethanol, 0.2% bromophenol blue, and 4% SDS for 10 min at 90°C.…”
Section: Methodsmentioning
confidence: 99%